2014
DOI: 10.4161/psb.29720
|View full text |Cite
|
Sign up to set email alerts
|

Root development under control of magnesium availability

Abstract: Roots are reported to be plastic in response to nutrient supply, but relatively little is known about their development in response to magnesium (Mg) availability. Here, we showed the influence of both low and high Mg availability on the development of roots including root hairs and highlighted insights into the regulatory role of Mg availability on root hair development and its mechanism in Arabidopsis with combining our published research. Mg concentration in roots decreased quickly after the removal of Mg f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
5
25
0
1
Order By: Relevance
“…2). Recently, Niu et al 19 reported that reactive oxygen species (ROS) and cytosolic Ca 2C could be the signal factors responding to MgSs, hence, validated the previous hypothesis that antioxidation might be one of the early responses to MgSs. 9,21,45 Generally, MgD blocks sugar transport through phloem from leaves to roots, this improves starch accumulation in leaves and feedback inhibits photosynthesis, increases ROS in cell, and consequently restrains plant growth.…”
Section: Signal Transduction Of Magnesium Stresses In Plantssupporting
confidence: 58%
“…2). Recently, Niu et al 19 reported that reactive oxygen species (ROS) and cytosolic Ca 2C could be the signal factors responding to MgSs, hence, validated the previous hypothesis that antioxidation might be one of the early responses to MgSs. 9,21,45 Generally, MgD blocks sugar transport through phloem from leaves to roots, this improves starch accumulation in leaves and feedback inhibits photosynthesis, increases ROS in cell, and consequently restrains plant growth.…”
Section: Signal Transduction Of Magnesium Stresses In Plantssupporting
confidence: 58%
“…The level of Mg in the soil is basically maintained by natural genesis and/or fertilization practice and thus both deficiency and excess of Mg should be taken into consideration during developing management strategies. Abnormal Mg status in soil resulting from either Mg depletion or Mg excess is generally considered negative for the growth of the plants [ 16 23 ]. Importantly, aside from its crucial role in a vast number of enzymatic reactions including nucleotide metabolism and the turnover of nucleic acids in transcription, splicing or replication, Mg has an additional prominent role as the central atom in the chlorophyll molecules of photosynthesizing organisms [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when treated with diphenylene iodonium (DPI, an NADPH-oxidase inhibitor) or 1,2-bis(o-aminophenoxy)ethane-N,N,N',N',-tetraacetic acid (BAPTA, a Ca 2+ chelator), the Ca 2+ concentration gradient was eliminated for the enhanced growth of root hair in low-Mg treatment (Frahry and Schopfer, 1998;Yoshioka et al, 2001;Kadota et al, 2004). Instead, root hair growth was blocked in high-Mg treatment and the inhibiting effect was restored when supplied with CaCl 2 or phenazine methosulfate (PMS, a ROS generator) in Arabidopsis (Zhang et al, 2009;Niu et al, 2014). The study outlined by Niu et al, (2014) showed that NADPH oxidase in root was positive regulated by low Mg and was inhibited by high Mg level, which is further evidence that Mg could control ROS to regulating root hair growth and development.…”
Section: Root Hair and Magnesium (Mg)mentioning
confidence: 65%
“…Instead, root hair growth was blocked in high-Mg treatment and the inhibiting effect was restored when supplied with CaCl 2 or phenazine methosulfate (PMS, a ROS generator) in Arabidopsis (Zhang et al, 2009;Niu et al, 2014). The study outlined by Niu et al, (2014) showed that NADPH oxidase in root was positive regulated by low Mg and was inhibited by high Mg level, which is further evidence that Mg could control ROS to regulating root hair growth and development. Therefore, the growth and development of root hair is closely related to Mg availability, which though ROS and Ca 2+ signaling.…”
Section: Root Hair and Magnesium (Mg)mentioning
confidence: 65%
See 1 more Smart Citation